A rapid and simple single‐step method for the purification of Toxoplasma gondii tachyzoites and bradyzoites. Issue 2 (26th September 2020) - El‐Ashram, Saeed; Zhang, Yu; Ji, Yongsheng; Salama, Dina; Mei, Kun; Zhili, Li; Shujian, Huang; Zhang, Haoji; Aboelhadid, Shawky M.; Alajmi, Reem A.; Metwally, Dina M.; El‐Khadragy, Manal F.; et al.
Abstract: This study describes a simple method for the large‐scale isolation of pure Toxoplasma gondii tachyzoites and bradyzoites. T. gondii tachyzoites were obtained from infected human foreskin fibroblasts (HFFs) and peritoneal exudates of mice, while tissue cysts containing bradyzoites were collected from chronically infected mice. Harvested cells and brain tissues were incubated in Hanks balanced salt solution (HBSS), containing 0.25% trypsin and 0.5% taurodeoxycholic acid (TDC) for 5 min. Subsequent washes in phosphate buffered saline (PBS) were conducted, and the cell viability of the preparations was good, as determined by flow cytometry and ability to reinfect HFF cells and propagate in mice. The purification procedure allowed for a rapid preparation of pure T. gondii tachyzoites and bradyzoites in sufficient quantity that can be used for downstream procedures. The advantage of the new method is that it is convenient and inexpensive. Abstract : We developed a rapid and simple method for purifying tachyzoites and bradyzoites with optimal yield and purity. The new proposed method has the following advantages: (1) zoites can be obtained quickly and easily; (2) the technique can be performed in low resource settings and capable of handling larger numbers of cells and tissues; (3) zoites obtained in this way are free of cellular debris; and (4) the viability and infectivity of tachyzoites, and bradyzoites are maintained. A more detailed study is required to explore the effect of trypsin on surface antigens of parasites.